Overview of the State of Forests and Forest Management in Turkmenistan - United Nations (United Nations, 2020)
The overview of the State of Forests and Forest Management in Turkmenistan aims to present the forest resources and the forest sector of the country, including trends in, and pressures on the resource, to describe the policies and institutions for the forest sector and to list the major challenges the sector faces, and the policy responses in place or planned. The study is a cooperative effort by the author, the UNECE/FAO secretariat and national experts, done with the use of the best available data. It attempts to cover all dimensions of sustainable forest management.